Inverted P3HT:PCBM organic solar cells on low carbon steel substrates. (August 2016) - Sowjanya Pali, L.; Ganesan, Palaniswamy; Garg, Ashish
Highlights: Organic solar cell on low carbon steel substrate. Effect of thickness and morphology of thin metal transparent conducting layer on device performance. Effect of thickness and morphology of ZnO and MoO3 in improving device efficiency. Optical field distribution within the active layer using transfer matrix method. Abstract: Solar cell device fabrication on opaque metallic substrates is limited by the transmission of light from top transparent electrode. Moreover, conductivity of the substrates requires insulation for cell integration in a module. In this manuscript, we report fabrication of inverted ITO-free organic solar cells on opaque steel substrates without use of any lithography with power conversion efficiencies of ca. 1.35%. The device structure was Steel/Insulator/Al/ZnO/P3HT:PC60 BM/MoO3 /Au. The insulated substrates were first planarized using a thin poly(methymethacrylate) or PMMA layer to minimize the substrate roughness and to enable the fabrication of subsequent layers with minimum roughness. We investigated the effect of thickness of various layers to maximize the performance of these devices with major emphasis on improving the transmission of top electrode to maximize the light absorption in the active layer blend. For best photovoltaic characteristics of the devices, thickness determination of thin transparent conducting layer of gold was carried out by conducting transmission, conductivity and morphological studies. Solution processed ZnO on Aluminum showed ridge like structure which provides larger interfacial area for the collection of electrons. Photoluminescence measurements on Active layer/MoO3 emphasize the importance of insertion of sufficiently thin MoO3 layer in the device in terms of efficient exciton dissociation.